Removal of organic contaminants by natural pine cone and pine leaves as adsorbent - Yagub, Musstafa; Sen, Tushar; Ang, Ha Ming (Engineers Australia, 2011, 2011)
The adsorption capacity of natural pine cone and pine leaves for removal of methylene blue (MB) from aqueous solution was investigated in a batch system. The effects of the process variables, such as contact time, initial dye concentration, pH, salt concentration and system temperature on the adsorption process were studied. The extent of methylene blue dye adsorption increased with increases in initial dye concentration, contact time, and solution pH but decreased with salt concentration and temperature of the system for pine cone-MB system. However, for pine leaves-MB system adsorption increased with increases in initial dye concentration, contact time, solution pH and temperature of the system but decreased with salt concentration. Equilibrium data were best represented by the Langmuir isotherm. The maximum monolayer adsorption capacity of pine cone and pine leaves biomass was 129.87 mg/g and 126.58 mg/g respectively at 30°C. The pseudo- first- order model and pseudo- second- order models were used to describe the Kinetic and Mechanism of adsorption process. Thermodynamic parameters such as standard Gibbs free energy (ΔG0), standard enthalpy (ΔH0), and standard entropy (ΔS0) were calculated.